Village financial accountability and local empowerment strategy in achieving Indonesia Emas 2045: A case study in Amplas Village - M. Safii Murad Daulay; Uswatun Hasanah; Ayunda Fatmasari; Oppie Meisya Tanjung; Oki Prayogi; Hajatina Hajatina (Priviet Social Sciences Journal, 2025)
This study aims to explore village financial accountability and management strategies implemented for community economic empowerment toward the Indonesia Emas 2045 vision, using Amplas Village in Percut Sei Tuan District as a case study. A descriptive qualitative method was applied through field practice and direct interviews with the village head and local residents of the village. The results show that the village has established a Merah Putih Cooperative as a collective platform for managing agricultural and livestock products, which is officially registered and plays a key role in improving access to capital and product values. Additionally, government support programs, such as the Family Hope Program (PKH) and microenterprise training, have encouraged local community participation in economic activities. However, challenges remain, including unequal aid distribution and a lack of routine outreach. The study concludes that financial accountability through cooperatives and participatory village management strategies has contributed positively to economic empowerment, although further improvements are needed in reporting transparency and equal access to programs. These findings are expected to provide input for village policymakers in designing community-based financial and empowerment policy.